Targeting anaplastic lymphoma kinase in neuroblastoma. Issue 5 (3rd April 2019) - Umapathy, Ganesh; Mendoza‐Garcia, Patricia; Hallberg, Bengt; Palmer, Ruth H.
Abstract : Over the last decade, anaplastic lymphoma kinase (ALK), a receptor tyrosine kinase (RTK), has been identified as a fusion partner in a diverse variety of translocation events resulting in oncogenic signaling in many different cancer types. In tumors where the full‐length ALK RTK itself is mutated, such as neuroblastoma, the picture regarding the role of ALK as an oncogenic driver is less clear. Neuroblastoma is a complex and heterogeneous tumor that arises from the neural crest derived peripheral nervous system. Although high‐risk neuroblastoma is rare, it often relapses and becomes refractory to treatment. Thus, neuroblastoma accounts for 10–15% of all childhood cancer deaths. Since most cases are in children under the age of 2, understanding the role and regulation of ALK during neural crest development is an important goal in addressing neuroblastoma tumorigenesis. An impressive array of tyrosine kinase inhibitors (TKIs) that act to inhibit ALK have been FDA approved for use in ALK‐driven cancers. ALK TKIs bind differently within the ATP‐binding pocket of the ALK kinase domain and have been associated with different resistance mutations within ALK itself that arise in response to therapeutic use, particularly in ALK‐fusion positive non‐small cell lung cancer (NSCLC). This patient population has highlighted the importance of considering the relevant ALK TKI to be used for a given ALK mutant variant. In this review, we discuss ALK in neuroblastoma, as well as the use of ALK TKIs and other strategies to inhibit tumor growth. Current efforts combining novel approaches and increasing our understanding of the oncogenic role of ALK in neuroblastoma are aimed at improving the efficacy of ALK TKIs as precision medicine options in the clinic.